An Exploration on New Product Development Process of Malaysian Small-Sized Automaker - Boejang, H.; Ariff, H.; Hassan, M. Z.; Esa, S.; Rauterberg, M. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
This paper focused on the identification and description of a new product development (NPD) approach adopted by one of the small-sized car producers in Malaysia. The NPD processes for European, Japanese and American auto makers have been studied and discussed in literature. However, the business strategy of NPD approach of small-sized car makers remains unidentified and less understood. This research involved semi-structured face-to-face interview sessions at several occasions with senior project managers and development team members, a senior product planning manager together with a selected first tier vendor. The information obtained through literature on the NPD process was used as secondary data to correlate with the data obtained from the primary source (interview). Results derived from both sources later were used to completely identify and describe the NPD process of this car maker. The results indicated that the NPD process of the automaker was not that distinct as compared with the generic product development of others. In addition, the findings also showed the automaker has adopted the concurrent engineering practices in the product development process. This paper also highlighted the importance of a formal NPD with regard to the frequency of the new product introduction and managing risks and uncertainty.